Dimensi Soteriologi Imperatif dalam Injil Matius - Haposan Silalahi; Elisamark Sitopu (Te Deum (Jurnal Teologi dan Pengembangan Pelayanan), 2025)
This study aims to analyze the imperative dimension of soteriology in the Gospel of Matthew. Using a library research method, it explores how salvation in Matthew is inseparably linked to the actions and obedience of believers. The findings show that Matthew presents salvation not merely as a passive gift but as something that demands an active response—a life of obedience. Like an unfruitful tree that is cut down, faith without action is considered incomplete. The imperative soteriology of Matthew is expressed through Jesus’ teachings that call believers to do the “will of God,” rooted in grace and the covenant of forgiveness through Christ. The Greek verb poieō (“to do”) plays a central role in Matthew’s soteriological vision, signifying wholehearted obedience to God’s commandments. This imperative element encourages a transformative faith, where believers demonstrate their salvation by actively living in alignment with God’s will in both attitude and action.